Targeted next-generation sequencing: a Swiss army knife for mycobacterial diagnostics?. Issue 3 (18th March 2021) - Mohamed, Sagal; Köser, Claudio U.; Salfinger, Max; Sougakoff, Wladimir; Heysell, Scott K.
The genus Mycobacterium encompasses almost 200 species that fall into four main groups [1]. Specifically, the Mycobacterium tuberculosis complex (MTBC), the causative agent of tuberculosis (TB) and leading cause of death by a single infectious agent, is distinguished from mycobacteria causing Buruli ulcer and leprosy [2, 3]. The remaining species are referred to as nontuberculous mycobacteria (NTM), which mainly cause lung disease and have become more frequent in many parts of the world, particularly amongst older patients [4]. Like a multifunctional Swiss army knife, Deeplex offers unprecedented versatility directly from the clinical sample and represents a welcome addition to the diagnostic and epidemiological toolbox https://bit.ly/38s6ukF